'When I can ride my bike, I think, am I at all as sick as they say?' An exploration of how men with advanced lung cancer form illness perceptions in everyday life. (16th November 2022) - Maersk, Jesper Larsen; Rosted, Elizabeth; Lindahl‐Jacobsen, Line
Abstract: Objective: The purpose of this study was to explore how men with advanced lung cancer form perceptions of their illness in everyday life and how this influences perceptions about rehabilitation. Methods: Constructivist grounded theory principles guided the collection and analysis of data from in‐depth interviews with 10 men with advanced lung cancer. Results: The findings show that the men's illness perception was fluid, contextual and formed by interrelated factors. Engaging in daily activities and maintaining everyday life was a strong influence on their illness perception. Conclusion: In order to make rehabilitation relevant to men with lung cancer, consideration should be given to how the men's everyday lives may be incorporated into the service provision.